Effect of Vitamin E Supplementation In Diluent on Fertility Parameters of Different Quality Fresh Bull Sperm - Putri, Sri Mardhiani Penta; Jaswandi, Jaswandi; Masrizal, Masrizal (Jurnal Sain Peternakan Indonesia, 2025)
This study aimed to determine the effect of vitamin E supplementation on tris-egg yolk diluent using different quality fresh semen. The research material was ejaculated from six Simmental bulls and then classified into standard quality (SQ) and low quality (LQ) according to progressive motility. The research method was experimental with a randomized factorial design (2X5), with the group by fresh semen with 3 replications. The first factor was the quality of fresh semen, while the second factor was the level of vitamin E addition (B0: 0mg/ml; B1: 0.5 mg/ml; B2: 1 mg/ml; B3: 1.5 mg/ml; and B4: 2 mg/ml). After thawing, the observation parameters were motility, viability, abnormality, plasma membrane integrity, and MDA levels.  The result shows that the quality of fresh semen has a very significant effect (p<0.01) on the motility of frozen semen (66.28±8.66%) and a significant impact (p<0.05) on the plasma membrane integrity (91.31±2.87%). The use of vitamin E at 1 mg/ml showed the best results on motility (66.11±7.64%), viability (70.19±12.13), abnormality (12.00±3.13), and MDA (2.11±0.77). This study concludes that adding vitamin E to the diluent can increase motility, viability, and plasma membrane integrity while reducing abnormality and MDA levels. Low-quality fresh semen can be processed into frozen semen after adding vitamin E. The best level of vitamin E addition is 1 mg/ml.